1993
DOI: 10.1177/095646249300400201
|View full text |Cite
|
Sign up to set email alerts
|

Streptococci and the Genital Tract

Abstract: Summary: Streptococci of Lancefield Group B (GBS) are known to cause maternal sepsis and neonatal infection, whereas streptococci Lancefield Group A (GAS) cause vulvo-vaginitis in both children and adults. Prevalence of SGB colonization of the lower genital tract of normal women is between 4-18%, with higher rates found in hospital personnel and delivery rooms. Such high carriage rates may be a significant factor in nosocomial transmission of GBS to neonates. Symptomatic infection is uncommon and usually secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…1,8,29 Neither infection showed any significant association with the suspected risk factor, in contrast to other studies. 21,30 Possibly, the small numbers of isolates could explain the absence of statistical significance.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…1,8,29 Neither infection showed any significant association with the suspected risk factor, in contrast to other studies. 21,30 Possibly, the small numbers of isolates could explain the absence of statistical significance.…”
Section: Discussioncontrasting
confidence: 53%
“…National and international comparisons are hampered because of the different methodology of studies. The majority of studies investigated the prevalence of each organism separately, 1,6,7,8 while others studied high-risk population groups. 1,9,10 In this study, the finding of G. vaginalis as the most commonly isolated organism, with a prevalence rate of 28%, is in agreement with other studies that showed different rates ranging from 9% to 53%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Group B beta-haemolytic streptococci are known to colonise the throat and lower female genital tract; prevalence is 4% to 18% [14]. Other causative organisms include Staphylococcus, Chlamydia trachomatis, Escherichia coli, Klebsiella pneumoniae, Bacteroides spp., Candida and anaerobic streptococci.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the relatively low carriage rate in normal flora, these findings suggest that Enterobacteriacea, Enterococcus spp., or S. agalactiae have roles in the infection and should not be considered as part of the normal vaginal flora in symptomatic women with microscopic evidence of inflammation [5]. The causitive role of S. aureus in vulvovaginitis has not been well researched, since the bacteria is known to colonize the genital tract in 4%-18% of healthy women [27]. Some studies showed that it is related to vaginal symptoms and signs [28].…”
Section: Discussionmentioning
confidence: 99%